Contemporary practices of strength and conditioning coaches in professional soccer - Weldon, Anthony; Duncan, Michael J.; Turner, Anthony; Sampaio, Jaime; Noon, Mark; Wong, Del; Lai, Vivian W. (Biology of Sport, 2021)
This study describes the contemporary practices of strength and conditioning coaches in professional soccer. Fifty-two strength and conditioning coaches from professional leagues across 18 countries completed an online survey, consisting of 45 questions, with eight sections: (a) background information, (b) muscular strength and power development, (c) speed development, (d) plyometrics, (e) flexibility development, (f) physical testing, (g) technology use, and (h) programing. A frequency analysis was used to assess and report responses to fixed response questions, and thematic-analysis used for open-ended questions to create clear, identifiable and distinct themes. All strength and conditioning coaches were educated to degree level or higher, 65% held strength and conditioning certifications and 54% held soccer coaching certifications. Concentric (100%) and eccentric (98%) modes of resistance were the most commonly prescribed, whereas the squat (including variations) (52%) was deemed the most important exercise for soccer players. Hang clean (33%) and multiple hops/lunges (89%) were the most programed Olympic weightlifting and plyometric exercises. Global Positioning Systems (94%) were the most utilized technology-based equipment. Time, scheduling and fixtures were the biggest issues faced, which made it difficult to periodize training programs and apply appropriate training loads. Furthermore, strength and conditioning coaches would like to further integrate technology to comprehensively monitor and test players, while also believing that technology will continue to be developed and integrated in the future. Strength and conditioning coaches from professional soccer can use the information from this study to review current practices and also provide ideas for diversifying or modifying future practices